Effects of Modifying Orthodontic Adhesive by Thymus Vulgaris and Lavandula Angustifolia Essential Oils on Compressive Strength - Reem Thamer Musleh; Ali R. Alkhatib; Sam'an Malik. Masudi (University of Mosul, College of Dentistry, 2024)
Aims: The aims of the current study were to investigated and compared the effects of different concentrations of Thymus vulgaris and Lavandula angustifolia essential oils incorporated in orthodontic adhesive on compressive strength. Materials and Methods: Thirty samples were prepared to be included in the study groups. They were constructed from cylinders of 6 mm in height and 4 mm in diameter for each one. The adhesive samples were modified by incorporating 1%, 3% of Thymus vulgaris and 1%, 3% Lavandula angustifolia essential oils separately. After curing of the modified adhesive, each sample was placed in a universal testing machine between its plate and arm that has a capacity of 1000 kN. The compressive strength was tested by using a crosshead speed of 0.5 mm/min. The force of the machine was delivered perpendicularly to the composite samples by a plate producing a compressive force on the sample. The applied force at fracture time was recorded in Newton, then it was converted into mega Pascal (MP) by dividing the applied force by the surface area of the composite samples. The data were statistically analysed at p <0.05. Results: The results revealed that 1% Lavandula angustifolia group showed the highest mean values of compressive strength among the groups except for the control. Whereas, Thymus vulgaris groups showed the lowest mean values of compressive strength. The remaining groups were distributed on statistical levels between the highest and lowest levels of mean value. One way analysis of variance demonstrated a significant difference within and between the mean values. Multiple comparisons showed a significant difference in compressive strength between control and of 3% Thymus vulgaris groups at (p < 0.05). Conclusions: Compressive strength recorded similar reduction behaviour for the two materials regarding the reduction in its value. However, the incorporation of 3% Thymus vulgaris showed evident decrease.